IMPLEMENTATION OF A WEB-BASED SPP PAYMENT INFORMATION SYSTEM AT SMA NEGERI 1 WATUBANGGA USING THE WATERFALL METHOD TO ENHANCE EFFICIENCY AND TRANSPARENCY - Bantun, Suharsono; Sari, Indri Purnama; Assagaf, Sayyed; Sari, Jayanti Yusmah (Jurnal Teknik Informatika (Jutif), 2024)
This research aims to develop and implement a website-based Education Development Contribution (SPP) payment information system at SMA Negeri 1 Watubangga using the Waterfall method. The general problem faced is the management of conventional SPP payments which is inefficient, prone to errors, and lacks transparency. In particular, SMA Negeri 1 Watubangga experienced difficulties in manually recording SPP payments which resulted in data accumulation, loss of payment cards, and errors in presenting reports. Needs analysis was carried out through interviews and observations with related parties, resulting in functional requirements such as student data management, SPP bill management, printing proof of payment, and payment reports that can be accessed by the school principal. Coding is done using HTML, CSS, JavaScript, and PHP, with a MySQL database. The WhiteBox test results show that this system is free from errors with cyclomatic complexity, region and independent path values ​​of 52. A total of 14 flowgraphs received good validation. User Acceptance Test (UAT) testing with 36 respondents, including treasurers, school principals and students, showed positive results with a final score of 64%, indicating this system is good and feasible to implement. Implementation of this system increases efficiency and transparency in managing SPP payments, as well as making access to information easier for students and schools. Challenges in user adaptation to new systems can be overcome with intensive training. This research proves that information technology can provide an effective solution in managing SPP payments and can be used as a model for other schools that face similar challenges.